Gangguan Stress Pasca Trauma Perempuan yang mengalami KDRT di Kabupaten Pinrang - Ikmal, Ikmal (Indonesian Journal of Islamic Counseling, 2025)
Post-traumatic stress disorder or what is commonly known as PTSD is a mental problem that occurs because someone experiences a traumatic event. Traumatic events that generally cause PTSD are accidents, sexual abuse, experiencing physical violence, and so on. However, this is not easy to research because it is personal. The thing that the writer fears most is that if the writer wants to dig deeper into the victim's traumatic incident, it will bring up feelings of trauma again, so the writer is very careful in taking research steps. The research method used is a qualitative method with case studies. The data source used is primary data, the data of which was obtained directly from interviews with the Pinrang Regency DP3A and victims of domestic violence in Pinrang Regency, while secondary data was obtained from books, documents and journals/previous research theses which are related to this research. The data analysis techniques consist of data reduction, data presentation, and verification/drawing conclusions. The results of the research show that firstly, victims of domestic violence really need a helping hand from their families to return and reconcile, accompany them and understand what they are experiencing because the trauma and shame they feel makes them weak. Social support in the form of advice and suggestions from family, village government and community leaders really helps them to solve problems. After being given social support, there are those who choose to separate and there are also those who stay. On average, victims of domestic violence treatment experienced significant PTSD so that at that time the victim's mental and physical condition really needed strong support. Second, the main triggers for domestic violence in Pinrang district are children, jealousy and economic problems. Acts of domestic violence experienced not only once or twice but often occur, causing the victim to feel excessive trauma. The way for victims to be free from this treatment is that some choose to separate and there are also those who survive to give each other a chance and improve each other.